2021
DOI: 10.1098/rsif.2020.0875
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and predicting the effect of social distancing and travel restrictions on COVID-19 spreading

Abstract: To date, the only effective means to respond to the spreading of the COVID-19 pandemic are non-pharmaceutical interventions (NPIs), which entail policies to reduce social activity and mobility restrictions. Quantifying their effect is difficult, but it is key to reducing their social and economic consequences. Here, we introduce a meta-population model based on temporal networks, calibrated on the COVID-19 outbreak data in Italy and applied to evaluate the outcomes of these two types of NPIs. Our approach comb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 49 publications
4
79
0
Order By: Relevance
“…Since the COVID outbreak, studies have shown that encouraging people to get vaccinated and continuing nonpharmaceutical control policies are effective ways to suppress the disease spread [35][36][37]. Consistently, we conclude that it is possible to ensure a healthy campus community associated with NPIs even at a lower immune level of 30%.…”
Section: Discussionsupporting
confidence: 79%
“…Since the COVID outbreak, studies have shown that encouraging people to get vaccinated and continuing nonpharmaceutical control policies are effective ways to suppress the disease spread [35][36][37]. Consistently, we conclude that it is possible to ensure a healthy campus community associated with NPIs even at a lower immune level of 30%.…”
Section: Discussionsupporting
confidence: 79%
“…As more Since the inception of the worldwide COVID-19 pandemic in January 2020, mathematical models have emerged as powerful tools to combat its spread. [5][6][7] In the first phase of the pandemic, models have been largely adopted to conduct what-if analyses on the effect of nonpharmaceutical interventions (NPIs) for the containment of the spread, [8][9][10][11][12] also considering their socio-economic and psychological impact. [13][14][15] More recently, models are gaining traction as decision support systems to design efficient vaccination campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an advantage of our formalism is its relative simplicity, paving the way to extend the results to more general scenarios. For example, the homogeneous assumption concerning the contacts of individuals within each subpopulation can be improved to account for the heterogeneous nature of human contacts 62,63 . In addition, we have restricted our study to the morphology of urban flows by neglecting the contribution coming from movements between different urban areas.…”
Section: Discussionmentioning
confidence: 99%